Amplification of Frequency-Modulated Similariton Pulses in Length-Inhomogeneous Active Fibers - I. O. Zolotovskii; D. I. Sementsov; A. A. Sysolyatin; A. S. Belanov; M. S. Yavtushenko (International Journal of Optics)
The possibility of an effective gain of the self-similar frequency-modulated (FM) wave packets is studied in the length-inhomogeneous active fibers. The dynamics of parabolic pulses with the constant chirp has been considered. The optimal profile for the change of the group-velocity dispersion corresponding to the optimal similariton pulse amplification has been obtained. It is shown that the use of FM pulses in the active (gain) and length-inhomogeneous optical fibers with the normal group-velocity dispersion can provide subpicosecond optical pulse amplification up to the energies higher than 1 nJ.